2014
DOI: 10.1371/journal.pone.0098924
|View full text |Cite
|
Sign up to set email alerts
|

ChR2 Mutants at L132 and T159 with Improved Operational Light Sensitivity for Vision Restoration

Abstract: The ectopic expression of microbial opsin-based optogenetic sensors, such as channelrhodopsin-2 (ChR2) in surviving inner retinal neurons, is a promising approach to restoring vision after retinal degeneration. However, a major limitation in using native ChR2 as a light sensor for vision restoration is the low light sensitivity of its expressing cells. Recently, two ChR2 mutations, T159C and L132C, were reported to produce higher photocurrents or have ultra light sensitivity. In this study, we created addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 31 publications
1
41
0
1
Order By: Relevance
“…Basically, a ChR with high light sensitivity requires production of a large photocurrent at low light stimulation, which is also defined as operational light sensitivity (referred to as light sensitivity for simplicity hereafter) (Mattis et al 2012). On the basis of this criterion, the L132C/T159S ChR2 mutant exhibits highest light sensitivity (Pan et al 2014a). A side-byside comparison of almost all the reported ChR variants revealed that the increase in the light sensitivity closely correlated with the slower kinetics or the increase in off-rate (Mattis et al 2012, Pan et al 2014a; this suggests that the increase in light sensitivity was mainly due to the prolonged channel opening, which decreases the temporal resolution.…”
Section: Development Of Optogenetic Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Basically, a ChR with high light sensitivity requires production of a large photocurrent at low light stimulation, which is also defined as operational light sensitivity (referred to as light sensitivity for simplicity hereafter) (Mattis et al 2012). On the basis of this criterion, the L132C/T159S ChR2 mutant exhibits highest light sensitivity (Pan et al 2014a). A side-byside comparison of almost all the reported ChR variants revealed that the increase in the light sensitivity closely correlated with the slower kinetics or the increase in off-rate (Mattis et al 2012, Pan et al 2014a; this suggests that the increase in light sensitivity was mainly due to the prolonged channel opening, which decreases the temporal resolution.…”
Section: Development Of Optogenetic Toolsmentioning
confidence: 99%
“…On the basis of this criterion, the L132C/T159S ChR2 mutant exhibits highest light sensitivity (Pan et al 2014a). A side-byside comparison of almost all the reported ChR variants revealed that the increase in the light sensitivity closely correlated with the slower kinetics or the increase in off-rate (Mattis et al 2012, Pan et al 2014a; this suggests that the increase in light sensitivity was mainly due to the prolonged channel opening, which decreases the temporal resolution. When expressed in retinal ganglion cells, the respective light sensitivities of the L132C/T159C and L132C/T159S ChR2 mutants were 1.5 and nearly 2 log units higher than in wild-type ChR2 (Figure 3), whereas the modulation of their spike activities in response to low light followed light flicker frequencies up to 20 and 10 Hz, respectively (Pan et al 2014a).…”
Section: Development Of Optogenetic Toolsmentioning
confidence: 99%
“…Moreover, properties that strongly depend on the target cells, such as expression level and membrane targeting, are of serious and equal importance, and these should be individually tested for each ChR variant and cell type, respectively. Finally, to help users choose a ChR variant (30,39) CatCh (ChR2 L132C) Enhanced Mg 2+ and Ca 2+ selectivity, large photocurrents, low inactivation (34,57) ChR2 T159C Large photocurrents, improved retinal binding affinity (7,74) CatCh + (ChR2 L132C-T159C) Enhanced Mg 2+ and Ca 2+ selectivity, large photocurrents, low inactivation, provides high light sensitivity to host cells, more stable expression than CatCh (52,57,63) ChETA (ChR2 E123T-T159C) Fast photocycle at the expense of reduced transported charge per absorbed photon, reduced voltage dependency of channel closing kinetics (7,21) Chronos Very fast photocycle, large photocurrents, inverse voltage dependency of off kinetics, provides high light sensitivity to host cells (33) Step-function rhodopsins …”
Section: Applications Of Channelrhodopsinsmentioning
confidence: 99%
“…6 As an alternative to retinal prosthesis, optogenetics can be used to restore vision by expressing optical neuromodulators such as channelrhodopsins or photochemically modified mammalian ion channels in residual retinal neurons. [7][8][9][10][11][12][13][14][15] Expression of channelrhodopsin in RGCs might allow greater spatial resolution and acuity than that achieved with current prosthetic devices. This has motivated a large body of proof-of-concept studies in rodents and other small animals, which have shown the feasibility of the approach, [7][8][9][10][16][17][18] and a first-in-human phase 1 clinical trial was initiated recently (ClinicalTrials.gov NCT02556736).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, studies assessing the feasibility of using microbial opsins for vision restoration have been carried out in small laboratory animals such as rodents, rabbits, and marmosets. [7][8][9][10]26,27 To our knowledge, the viral doses and construct optimizations necessary to obtain functional optogenetic readout have not yet been investigated in macaques.…”
Section: Introductionmentioning
confidence: 99%